The Influence of the Team Games Tournament (TGT) Model Assisted by Wordwall on Students' Learning Activities and Outcomes in Digestive System Material - Much Fadli Putra Syaeli; Nugrahaningsih (Universitas Negeri Semarang, 2025)
This study aimed to analyze the effect of the TGT (Teams Games Tournament) learning model assisted by Wordwall on student activity and cognitive learning outcomes in the digestive system material. The research employed a one-shot case study design, with the subjects being students of classes XI.1 and XI.2 at SMA Negeri 1 Bukateja, selected through purposive sampling. The independent variable in this study was the TGT learning model assisted by Wordwall, while the dependent variables were student activity and cognitive learning outcomes. The research results showed that student activity indikators, including visual, oral, listening, motoric, and mental aspects, achieved an average activity percentage of 87.5% by the fourth meeting, categorized as excellent. Cognitive learning outcomes also demonstrated a significant improvement, with an average N-gain score of 0.81 (high category). The highest improvement was observed in the understanding indikator (C2), which increased by 34%. The findings revealed that the TGT learning model assisted by Wordwall positively impacted both dependent variables. This study concludes that the TGT learning model assisted by Wordwall is effective in enhancing student activity and cognitive learning outcomes.